Development of high performance low-pass filter for anti-sway control of a gantry crane system - Fatin Roziana, Misran (2009)
This project proposes the applications and performance of Low - pass filter for anti - sway control of a gantry crane system. The control objective is to control and reduce residual sway angle of the pendulum by using feed forward approach. An unshaped bang - bang torque input is used to determine the characteristic parameters of the system for the design and evaluation of the Low - pass filter techniques. Experiment results of the response of gantry crane to the input are presented in time and frequency domains. The effects of the order of the filtered Low - pass filter on the performance of the system are investigated. Finally, a comparative assessment of the amplitude polarities of the system performance is presented and discussed.